Microbiome-Guided Exploration of the Microbial Assemblage of the Exotic Beverage “Insect Tea” Native to Southwestern China - Mao, Xin; Kusstatscher, Peter; Li, Haoxi; Chen, Xiaoyulong; Berg, Gabriele; Yang, Maofa; Cernava, Tomislav (Frontiers in Microbiology, 2020)
Insect tea is a unique beverage that is native to Southwestern China and traditionally produced by local farmers in an elaborate process. It consists of insect larvae excrements that are commonly obtained from meal moths (Pyralis farinalis LINNAEUS, 1758) reared on a specific plant-based diet. We have reconstructed the whole production process under laboratory conditions in order to obtain microbiome-level insights into this uncommon beverage and to trace back the origin of prevalent bacteria in the final product. The bacterial community composition was specific for each production stage, with a high proportion of Streptomycetacea, Pseudonocaridaceae, Enterococcaceae, and Enterobacteriaceae in the insect tea. A large proportion of constituents was traced back to the producing insect (13.2%) and its excrements (43.8%), while the initial plant-based substrate for tea production was found to contribute only 0.6% of traceable bacteria to the final product. Moreover, an enrichment of Enterobactericeae was observed during the analyzed process steps and verified with complementary analyses. Cultivation experiments indicated a high occurrence of viable bacteria in the tea with 2.7 × 105 ± 1.2 × 105 cfu g-1. Isolated bacteria included Bordetella petrii and Enterococcus spp. that were recovered from a commercial product. By implementing an integrative approach insect tea was shown to harbor a species-rich bacterial community that can be traced back to plant- and mainly insect-associated microbiomes. Moreover, the microbial profile of insect tea was found to be so far unique for a food product and containeds several bacterial groups that are considered as food contaminants from the current perspective or yet unreported in products suitable for human consumption. Due to the high number of viable bacteria, the tea harbors a so far undescribed, dynamic component that might have implications for human health.